A study of Human Epidermal Growth factor receptor-2 [HER-2] in Carcinoma Oesophagus [Single Institutional Tertiary cancer centre study from North-East part of India] - Deepjyoti Kalita; Srinivas Bannoth; Joydeep Purkayastha; Abhijit Talukdar; Gaurav Das (Wolters Kluwer Medknow Publications, 2021)
Background: Oesophageal cancer both squamous cell [SCC] and adenocarcinoma have poor outcomes with high morbidity and mortality. Our hospital-based registry for year 2017-2018 showed that oesophageal cancer constituted 22.7% of annual case load. The main objective of this study was to determine the presence of HER-2 receptors in patients with oesophageal carcinoma in our region. Methodology: From September 2018 to September 2019, data regarding expression of HER-2 receptors was analysed in 133 patients of oesophageal carcinoma. Data were statistically described as frequencies (number of cases) and percentages where appropriate. Chi-square and Fischer's exact test was used to find out the association between categorical variables. A P value less than 0.05 was considered as statistical significant at 95% confidence interval. The statistical analysis was performed using SSPS [statistical package for the social sciences] software version 17.0. Results: A total of 133 patients were taken into study. Majority of patients were males (96) with mean age of 52 years. Squamous cell carcinoma was predominant histology. HER-2 receptor positivity was seen in 6.01% of patients. Patients with HER-2 receptor positivity presented in advanced stage with poor functional status and poor grades of differentiation. Statistically significant correlation of Her-2 expression was seen with stage (p = 0.001) and pathology of tumour (p = 0.0001). Conclusion: Squamous cell carcinoma of oesophagus still predominates in North-eastern part of India. For studying the role of effective targeted therapies knowledge of frequency of HER-2 receptor positivity is of utmost importance in our population, and our study aims to answer this question. The present study shows low prevalence of HER-2 neu overexpression in our community, probably due to disproportionately high incidence of SCC compared to adenocarcinoma. Patients with HER-2 receptor positivity presented in advanced stage with poor functional status and poor grades of differentiation.